PEMBERANTASAN KORUPSI:: REFLEKSI BIBLIS ATAS PENYUCIAN BAIT ALLAH BERDASARKAN INJIL MATIUS 21:12-17 - Rumyaan, Imelda Febriyanti (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2021)
The story of Jesus purifying the temple in Matthew 21:12-17 is an important event in the life of Jesus which illustrates His attitude towards deviations and abuses in the church. This study aims to explain by using the exegesis analysis method in analyzing the story and its implications for church officials. In this study, exegetical analysis is used to explore the meaning of the text more deeply. Through an analysis of the historical, cultural and theological context, the researcher deepens understanding of the background of this story and the purpose for which it was written. This approach allows the researcher to interpret the text accurately, identify important elements in the story, and explore relevant implications for church officials. The results of the analysis show that Jesus' act of purifying the Temple was a rejection of corruption and abuse of power. This research contributes to the understanding of Jesus' attitude towards corruption in the church context. The resulting implications can be a guide for pastoral agents in carrying out church services that are clean, just, and meaningful to society. In addition, this research also provides a deeper understanding of the social, theological, and practical context of the story of Jesus purifying the Temple.